High School Teachers' Views on E-Learning Implementation Barriers During the COVID-19 Pandemic in Ramallah and Al-Bireh Directorate - Al- Ramahi, Rola; Ramahi, Refa' (Dirasat: Educational Sciences, 2023)
Objectives: This study investigates the e-learning barriers experienced by Palestinian high school mathematics and science teachers in Ramallah and Al-Bireh Directorate amid the COVID-19 pandemic and assesses the differences in teachers’ views of these barriers. Methods: A Stratified random sample that consisted of (104) participants from Ramallah and Al Bireh Directorate was recruited. Electronic questionnaires were used, and the descriptive statistical analysis was conducted to answer the research questions. The mean and standard deviations of responses for all the barrier options were calculated. An independent t-test and ANOVA were employed to examine differences between barriers according to the participants’ perceptions. The Scheffé test was also used to examine the differences between groups. Results: The findings showed that the level of barriers was high, with the highest barriers being at the students' level, followed by the curriculum level. The study found no statistically significant effect of specialization on the levels of barriers at school, curriculum, or academic qualifications. Conclusions: This research highlights the importance of overcoming learning barriers while maximizing the benefits of e-learning, emphasizing the significance of teachers' views during and after the pandemic.